Răspuns :
a² - b² = 24
3a + 3b = 6
============
a - b = ?
============
1) a² - b² = 24
( a - b)( a + b) = 24 ( 1)
2) 3a + 3b = 6
3( a + b) = 6
a + b = 6/ 3
a + b = 2 ( 2)
3) Din relatiile ( 1) si ( 2) ⇒ ( a - b)( a + b) = 24
( a - b) · 2 = 24
a - b = 24 / 2
a - b = 12
3a + 3b = 6
============
a - b = ?
============
1) a² - b² = 24
( a - b)( a + b) = 24 ( 1)
2) 3a + 3b = 6
3( a + b) = 6
a + b = 6/ 3
a + b = 2 ( 2)
3) Din relatiile ( 1) si ( 2) ⇒ ( a - b)( a + b) = 24
( a - b) · 2 = 24
a - b = 24 / 2
a - b = 12